Does interprofessional simulation increase self-efficacy: a comparative study - Peter Jaye; Gabriel Reedy; Alastair Ross; Colm Watters; Nicola J Morgan; Rhodri Handslip (BMJ Open)
Objectives In this work, we have compared uniprofessional and interprofessional versions of a simulation education intervention, in an attempt to understand more about whether it improves trainees’ self-efficacy.Background Interprofessionalism has been climbing the healthcare agenda for over 50 years. Simulation education attempts to create an environment for healthcare professionals to learn, without potential safety risks for patients. Integrating simulation and interprofessional education can provide benefits to individual learners.Setting The intervention took place in a high-fidelity simulation facility located on the campus of a large urban hospital. The centre provides educational activities for an Academic Health Sciences Centre. Approximately 2500 staff are trained at the centre each year.Participants One hundred and fifteen nurses and midwives along with 156 doctors, all within the early years of their postgraduate experience participated. All were included on the basis of their ongoing postgraduate education.Methods Each course was a one-day simulation course incorporating five clinical and one communication scenarios. After each a facilitated debriefing took place. A mixed methods approach utilised precourse and postcourse questionnaires measuring self-efficacy in managing emergency situations, communication, teamwork and leadership.Results Thematic analysis of qualitative data showed improvements in communication/teamwork and leadership, for doctors and nurses undergoing simulation training. These findings were confirmed by statistical analysis showing that confidence ratings improved in nurses and doctors overall (p<0.001). Improved outcomes from baseline were observed for interprofessional versus uniprofessional trained nurses (n=115; p<0.001). Postcourse ratings for doctors showed that interprofessional training was significantly associated with better final outcomes for a communication/teamwork dimension (n=156; p<0.05).Conclusions This study provides evidence that simulation training enhances participants’ self-efficacy in clinical situations. It also leads to increases in their perceived abilities relating to communication/teamwork and leadership/management of clinical scenarios. Interprofessional training showed increased positive effects on self-efficacy for nurses and doctors.